1989
DOI: 10.1128/jb.171.5.2563-2572.1989
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of bacteriophage lambda cIII gene: mRNA structural requirements for translation initiation

Abstract: The bacteriophage A cIl gene product regulates the lysogenic pathway. The cIl gene is located in the leftward operon, which is transcribed from the PL promoter. We have previously shown (S. Altuvia and A. B. Oppenheim, J. Bacteriol. 167:415-419, 1986) that mutations that show elevated expression lie within the clll coding sequence. We isolated mutants that show decreased CIII activity. AUl the mutations were found to cause a drastic reduction in the rate of initiation of cHl translation. Several mutations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Plasmid pSTD61 (3) carries the ATPasenegative hflB gene cloned downstream of the lac promoter in pHSG575. Plasmid ptaccIII (27) carries the CIII gene under control of the IPTG (isopropyl-␤-Dthiogalactopyranoside)-inducible tac promoter of the ampicillin-resistant vector ptac 12H. Plasmid pCG179 (42) carries the rpoH gene under control of the tac promoter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid pSTD61 (3) carries the ATPasenegative hflB gene cloned downstream of the lac promoter in pHSG575. Plasmid ptaccIII (27) carries the CIII gene under control of the IPTG (isopropyl-␤-Dthiogalactopyranoside)-inducible tac promoter of the ampicillin-resistant vector ptac 12H. Plasmid pCG179 (42) carries the rpoH gene under control of the tac promoter.…”
Section: Methodsmentioning
confidence: 99%
“…cIII is itself unstable (27), implying the existence of a proteolytic system capable of degrading it. The known properties of cIII-stabilization of cII and 32 and growth inhibition of the host cell-could be explained if cIII inhibits or competes efficiently for HflB.…”
mentioning
confidence: 99%
“…Previous experiments have shown that the host protein RNase III is required for efficient cIIl translation (2). In addition, genetic and biochemical evidence demonstrated that the region around the clII ribosome-binding site is found in two alternative conformations, only one of which is translated (1,16). We suggested that these features are related to regulation of clll expression at the translational level.…”
mentioning
confidence: 75%
“…In HK022, however, in contrast to X, no additional cleavage sites could be detected within the coding region (3a; data not shown). (1,2,16) in spite of extensive sequence dissimilarities between the HK022 and A clII coding regions (18) (Fig. 7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation